The distribution of picoplankton and nanoplankton in Kongsfjorden, Svalbard during late summer 2006 - Wang, Guizhong; 王桂忠; Guo, Chaoying; Luo, Wei（ Polar Res Inst China, SOA Key Lab Polar Sci, Shanghai 200136, Peoples R China）; Cai, Minghong（ Polar Res Inst China, SOA Key Lab Polar Sci, Shanghai 200136, Peoples R China）; He, Jianfeng（ Polar Res Inst China, SOA Key Lab Polar Sci, Shanghai 200136, Peoples R China） (Polar Biology, 2009)
Abundance and biomass of pico- (< 2 mu m) and nanoplankton (2-20 mu m) were investigated in relation to hydrography in Kongsfjorden, Svalbard (79A degrees N, 12A degrees E) during late summer 2006. Autotrophic and heterotrophic picoplankton abundance ranged from 0.1 x 10(6) to 35.2 x 10(6) cells L-1 and from 0.4 x 10(6) to 20.3 x 10(6) cells L-1, respectively. The highest number of bacteria in the entire water column was recorded at station 2 at 10 m (22.3 x 10(8) cells L-1); the lowest concentration was observed at station 1 (6.0 x 10(8) cells L-1). The abundance of autotrophic and heterotrophic nanoplankton varied from 0.4 x 10(5) cells L-1 to 46 x 10(5) cells L-1 and from 0.3 x 10(6) to 9.1 x 10(6) cells L-1, respectively. Our results demonstrated that heterotrophic nanoflagellates and bacteria in Kongsfjorden microbial community were relatively important. The structure of plankton communities integrated with environmental variables could act as indicators of the variability of the inflow of Atlantic Water into Kongsfjorden.